2011
DOI: 10.2176/nmc.51.857
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Fibrous Dysplasia: Reconstruction With Dysplastic Bone -Case Report-

Abstract: A 10-year-old girl presented with facial asymmetry associated with bulging of the right fronto-orbital region with no symptoms. Computed tomography demonstrated enlargement of the right zygomatic, frontal, ethmoid, and sphenoid bones. Abnormal proliferation of the bone had obliterated the sphenoid, right frontal sinus, and right ethmoid sinuses. These radiological findings suggested right optic nerve compression due to fibrous dysplasia. Right optic canal decompression was performed. In preparation for recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…10 The reported recurrence rate of FD lesions is variable, mostly between 25% and 55%. 16,23 In a series of 18 patients who underwent optic nerve decompression for orbital FD, Cutler et al 11 reported full encasement of the optic nerve on postoperative cranial CT scans in 15 (83%) of them, but only 2 of the 15 patients experienced symptoms of optic neuropathy. However, it was not known whether this was due to incomplete decompression or regrowth.…”
Section: Discussionmentioning
confidence: 99%
“…10 The reported recurrence rate of FD lesions is variable, mostly between 25% and 55%. 16,23 In a series of 18 patients who underwent optic nerve decompression for orbital FD, Cutler et al 11 reported full encasement of the optic nerve on postoperative cranial CT scans in 15 (83%) of them, but only 2 of the 15 patients experienced symptoms of optic neuropathy. However, it was not known whether this was due to incomplete decompression or regrowth.…”
Section: Discussionmentioning
confidence: 99%